PENGARUH PENGANGGARAN PARTISIPATIF PADA BUDGETARY SLACK DENGAN ASIMETRI INFORMASI, SELF ESTEEM, LOCUS OF CONTROL DAN KAPASITAS INDIVIDU SEBAGAI VARIABEL MODERASI - Ardianti, Putu Novia Hapsari; Suardhika, I Made Sadha; Suputra, I D. G. Dharma (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 04.NO.05.TAHUN 2015, 2015)
Budgetary participation not always has a linear effect on budgetary slack. This is because the contingency factors, four of them are asymmetry information, self-esteem, locus of control, and individual capacity. The research aimed to determine whether asymmetry information, self esteem, locus of control, and individual capacity capability to moderate the effects of participatory budgeting on budgetary slack. The data was collected using questionnaire. The amount of samples in this research were 110 echelon SKPD’s Jembrana selected by purposive sampling method. The analysis technique used regression analysis moderation. The result showed that participatory budgeting had a positive effect on budgetary slack. Self-esteem and locus of control weaken the effect of participatory budgeting on the budgetary slack, while asymmetry information is not be able to strengthen the effect of participatory budgeting on budgetary slack, and the individual capacity is not be able to weaken the effect of participatory budgeting on budgetary slack.
Keywords: Budgetary Slack, Penganggaran Partisipatif, Asimetri Informasi, Self Esteem, Locus of Control, Kapasitas Individu